2005
DOI: 10.1038/sj.cgt.7700835
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic adenovirus CG7870 in combination with radiation demonstrates synergistic enhancements of antitumor efficacy without loss of specificity

Abstract: Conditionally replicating adenoviruses that selectively replicate in tumor cells, but not in normal cells, are being explored as virotherapeutic agents for cancer. A prostate-specific oncolytic adenovirus, CG7870 is currently being evaluated in phase 1/2 clinical trials for the treatment of prostate cancer. To decrease the effective dose and further increase the therapeutic efficacy of CG7870, the combination of virotherapy with radiation therapy was explored in this study. CG7870 is an oncolytic adenovirus in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 12 publications
2
68
0
Order By: Relevance
“…We and others have previously shown that IR increased oncolytic HSV-1 replication. [11][12][13][14][15][16][17][18][19][20][21][22][23] The hypothesis tested in this series of experiments was that if varying the timing of IR in relation to the timing of viral injection would result in a further enhancement of viral replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously shown that IR increased oncolytic HSV-1 replication. [11][12][13][14][15][16][17][18][19][20][21][22][23] The hypothesis tested in this series of experiments was that if varying the timing of IR in relation to the timing of viral injection would result in a further enhancement of viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23] Specifically, g 1 34.5 deleted HSV-1 combined with IR resulted in increased viral replication and glioma-xenograft regression in hindlimb and orthotopic preclinical murine glioma models. 11,17 Mechanistic studies have elucidated multiple pathways through which IR enhances viral replication.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] A combination of CV787 along with radiotherapy significantly increased antitumor efficacy compared to either agent alone. 21 All of these studies intend to enhance cancer selective replication. For more details of adenovirus selective replication and oncolysis, several excellent reviews are available.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Additional therapeutic interventions are required to obtain greater tumour reductions. 5,6 For example, radiotherapy has been used in conjunction with the well-characterized oncolytic adenovirus ONYX-015 with beneficial responses. 7 More recently, administration of the prodrug ZD2767P in combination with an oncolytic adenovirus encoding the prodrug-activating enzyme carboxypeptidase G2 was shown to be highly effective in a murine model of colorectal carcinoma.…”
Section: Introductionmentioning
confidence: 99%